Ethanolic Extract of Hedyotis corymbosa L. Increases Cytotoxic Activity of Doxorubicin on MCF-7 Breast Cancer Cell - Haryanti, Sari; Junedi, Sendy; Meiyanto, Edy (Indonesian Journal of Biotechnology, 2009)
Hedyotis corymbosa L. with ursolic acid as the main compound is one of the plants that has been used for traditional medicine including to cure breast cancer disease. The aim of this research is to examine the cytotoxic activity of rumput mutiara herb ethanolic extract (ERM) and its effect in combination with doxorubicin against MCF-7 breast cancer cell line as cell model of doxorubicin resistance. Hedyotis corymbosa L. herb powder extraction was done by maceration using ethanol 96% then the extract is detected for ursolic acid content. Cell viability assay of ERM, doxorubicin and  the combination of ERM and doxorubicin treatments were carried out by MTT assay to determine IC50 and CI (Combination Index). Cell cycle distribution was determined by flowcytometry. Apoptosis assay was performed by ethidum bromide-acridine orange DNA staining method. Investigation on Bcl-2 expression was determined by immunocytochemistry method. Thin Layer Chromatography of ERM had similar Rf with ursolic acid standard: 0,6. ERM and doxorubicin inhibited cell growth against MCF-7 with IC50  of 77 µg/mL and 349 nM (0,19 µg/mL) respectively. Combination of ERM and doxorubicin showed synergistic effect (CI 0.66-0.99). Combination of 25 ìg/mL ERM- 200 nM doxorubicin induced apoptosis and decreased Bcl-2 expression but showed no cell accumulation on cell cycle. Doxorubicin induced high cell accumulation in G2/M phase, but ERM at the concentration of 25 ìg/mL had a low effect in G1 phase, and ERM IC50 did not induce cell accumulation otherwise apoptosis. These results concluded that the apoptosis mechanism of combination doxorubicin-ERM is mediated by cell cycle arrest and non cell cycle arrest. Therefore ERM has a potential activity to be developed as co-chemotherapeutic agent.